2021
DOI: 10.18632/aging.202785
|View full text |Cite
|
Sign up to set email alerts
|

Silencing long non-coding RNA MIAT ameliorates myocardial dysfunction induced by myocardial infarction via MIAT/miR-10a-5p/EGR2 axis

Abstract: Long non-coding RNA (lncRNA) myocardial infarction-associated transcript (MIAT) has been widely-demonstrated to function as diagnostic markers for acute myocardial infarction (MI). This study was designed to explore the modulatory role of MIAT and its underlying molecular mechanism in MI. Firstly, MI mouse model was developed via ligation of the descending branch of the left coronary artery, and cell model was established through exposure to hypoxic conditions . On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…It acts as a sponge for miR-1a in cardiomyocytes and exaggerates acute myocardial infarction via elevating the expression of early growth response gene-2 (EGR2). 21 Besides, it promotes p65 nuclear translocation and activates NF-kappaB signalling, resulting in elevated expression of cleaved-caspase-3 and Bax and downregulation of Bcl-2 in cardiomyocytes after I/R injury. 22 In cerebral microvascular endothelial cells, it sponges miR-204 and increases the expression of high mobility group box-1 protein (HMGB1), leading to enhanced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It acts as a sponge for miR-1a in cardiomyocytes and exaggerates acute myocardial infarction via elevating the expression of early growth response gene-2 (EGR2). 21 Besides, it promotes p65 nuclear translocation and activates NF-kappaB signalling, resulting in elevated expression of cleaved-caspase-3 and Bax and downregulation of Bcl-2 in cardiomyocytes after I/R injury. 22 In cerebral microvascular endothelial cells, it sponges miR-204 and increases the expression of high mobility group box-1 protein (HMGB1), leading to enhanced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Acute myocardial infarction/myocardial infarction presents with severe cardiomyocyte pyroptosis (Tibaut & Mekis, 2017). LncRNA MIAT acts as a crucial regulator in cardiomyocyte death and modulates the expression of other genes via binding to SF1 (Cao & Ma, 2021;Ip & Nakagawa, 2012). Moreover, CGRP targeted by SF1 splicing pre-mRNA plays an inhibitory role in cardiomyocyte death Zhou & Lou, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that lncRNA MIAT could act as a diagnostic marker for MI (Cao & Ma, 2021). To explore the regulatory mechanism of lncRNA MIAT in MI, H9C2 cells were subjected to hypoxia for 12 h to simulate MI in vitro.…”
Section: Lncrna Miat Was Overexpressed In Hypoxia-induced H9c2 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…PLA2G2A [61], CCL23 [62], CD53 [63], TREML4 [64], TREM2 [65], CD180 [66], HPSE (heparanase) [67], CELA2A [68], TNFRSF4 [69], AMBP (alpha-1-microglobulin/bikunin precursor) [70], SOX18 [71], PANX2 [72], RSPO2 [73], COMP (cartilage oligomeric matrix protein) [74], ASGR1 [75] and NOXA1 [76] are involved in progression of atherosclerosis. A previous study reported that S100A9 [77], ADORA3 [78], IL1R2 [79], FPR1 [80], CCL20 [81], CD163 [82], S100A8 [83], TLR2 [84], HAS2 [85], PTX3 [86], TIMP4 [87], AREG (amphiregulin) [88], LBP (lipopolysaccharide binding protein) [89], IL18R1 [90], ALOX5AP [91], RETN (resistin) [92], F13A1 [93], FPR2 [94], SAA1 [95], FLT3 [96], AQP4 [97], FCER1G [98], CCL18 [99], HP (haptoglobin) [100], CDK1 [101], SLC7A11 [102], CFTR (CF transmembrane conductance regulator) [103], F8 [104], STC1[44], IL18RAP [90], TIMP3 [105], PDE4D [106], CYP4A11 [107], SCN10A [108], APOB (apolipoprotein B) [109], ACE (angiotensin I converting enzyme) [110], PENK (proenkephalin) [111], HSPB6 [112], TLR9 [113], EGR1 [114], CACNG8 [115], FOXD3 [116], DBH (dopamine beta-hydroxylase) [117], FOXP3 [118], GLP1R [119], IL34 [120], CCN1 [121], ADRA2A [122], BGN (biglycan) [123], NOS2 [124], AGRN (agrin) [125], DRD1 [126], GNB3 [127], EGR2 [128], MDK (midkine) [129], NOTCH3 [130], AZIN2 [131], NOTCH1 [132], LOX...…”
Section: Discussionmentioning
confidence: 99%